International Media and Local Programming: The Case of Kuwait - Satti, Mohamed (2013)
The last decade has witnessed the acceleration of the phenomenon of media systems going global. Whereas media entities had previously relied on a national audience, going global has promised exposure to an increasingly diverse and sophisticated subscriber base. Although globalization is not a new occurrence, the global presence of media and its targeting of an international audience is a relatively new one. Particularly in the last two decades, media entities have increasingly targeted an international audience as a means of extending their reach and influence. While global media systems now have the ability to distribute media content to a worldwide audience, this phenomenon has undoubtedly created some concerns, especially in small markets such as Kuwait in the Gulf. This study will examine the proliferation of international programming in Kuwaiti film and television. The results will show that while nonKuwaiti, primarily U.S., content dominates movie theaters, Kuwaiti television preserves a stronger sense of national identity through its programming, thus showing the limits of globalization on local media markets.